Developing E-Learning based English Reading Materials for the Tenth Year Multimedia Students of SMK N 3 Singaraja - Trika Adi Ana, I Ketut (Jurnal Pendidikan dan Pembelajaran Bahasa Indonesia, 2012)
Abstract This study was a research and development (R&D), which aimed at (1) developing types of reading materials that are needed by the tenth year multimedia students of SMK N 3 Singaraja; finding out (2) the content validity of the developed material; (3) the quality of the developed material based on the criteria of good ESP material and good e-learning; and (4) whether or not the developed material could improve the reading comprehension of the tenth year multimedia students of SMK N 3 Singaraja. This study followed the R&D design by Lee and Owens. This design involves: need analysis, design, development, implementation, and evaluation. This study was conducted at SMK N 3 Singaraja, the subjects of the study being the students of class X MM 2. The data were collected through questionnaire, interview, expert judgment sheet, scoring rubric, and tests. The data from the result of observation, interview and questionnaire during the need analysis process were analyzed using Interactive Data Analysis Model. The result of the expert judgment in validating the content validity of the developed material was analyzed using Interrater Agreement Model. While the result of the scoring rubrics in measuring the quality of the developed material based on the criteria of good ESP material and good e-learning material were analyzed using Theoretic Ideal Reference. The result of this study shows that: (1) the tenth year multimedia students of SMK N 3 Singaraja need specific English materials that are related to their future job or study. The existing syllabus and material did not cover their needs since the syllabus and the material were designed to be used for all departments in SMKN 3 Singaraja, namely: Electricity Installation, Multimedia, Audio Video, Computer and Networking, Light Vehicle, Motor Cycle, Building Construction, and Engineering Departments; (2) based on the validation process that was conducted through expert judgment, it was confirmed that the developed material had a very high validity; (3) from the result of the expert judgment based on the criteria of good ESP material and good e-learning material, the developed material was categorized into very good material; and (4) the result of the field study shows that the developed material could improve the students? reading comprehension. It can be seen from the result of pre-test, post-test I, and post-test II that measured the students? reading comprehension. The students? mean score for those tests, which reflect the students? reading comprehension, increased from 40.9 in pre-test, to 66.3 in post-test I, and 79.1 in post-test II. Based on the result of the questionnaire, the students had strongly positive attitude toward the developed material; and (5) from the observation in developing and implementing the developed material, the problems that were found can be classified into technical and financial problems. Keywords: need analysis, e-learning, English reading material, R&D